Synthesis, characterization and gas separation properties of novel polyimides containing cardo and tert-butyl-m-terphenyl moieties - L. A. Bermejo; C. Alvarez; E. M. Maya; C. Garcia; J. G. de la Campa; A. E. Lozano (eXPRESS Polymer Letters, 2018)
A series of aromatic polyimides has been obtained by the reaction of two dianhydrides, the commercial 2,2′-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) and another having a 5′-tert-butyl-m-terphenyl moiety (BTPDA), with several diamines, including two that have a cardo structure (derived from 9H-fluorene), one of them bearing methyl groups ortho to the amino functionalities (TMeCardo). The solubility, and also the thermal, mechanical, and gas separation properties of the corresponding polyimide membranes were evaluated and compared in order to explore the effect of the different groups in the polyimide backbone. The novel polyimides, which were derived from BTPDA and the cardo diamines, showed high thermal stability, excellent solubility in organic solvents and good gas separation properties, especially the polyimide that bore the ortho methyl substituents. The behavior was especially good for the pair O2/N2, where the TMeCardo polymer overpassed the Robeson upper bound.